1997
DOI: 10.1021/jp961872j
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Surface Melting in Confined Clusters:  Ar13in Zeolite L

Abstract: Monte Carlo and molecular dynamics simulations on an Ar 13 cluster in zeolite L have been carried out at a series of temperatures to understand the rigid-nonrigid transition corresponding to the solid-liquid transition exhibited by the free Ar 13 cluster. The icosahedral geometry of the free cluster is no longer preferred when the cluster is confined in the zeolite. The root-mean-squared pair distance fluctuation, δ, exhibits a sharp, well-defined rigid-nonrigid transition at 17 K as compared to 27 K for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This is attributed to the suppression of vibrational motion of the surface atoms by the interface epitaxy. The melting starts from the centre and proceeds towards the surface [114] for embedded nanoparticles, while the melting starts from the surface and proceeds towards the centre for free nanoparticles.…”
Section: Superheating Of Nanoparticlesmentioning
confidence: 99%
“…This is attributed to the suppression of vibrational motion of the surface atoms by the interface epitaxy. The melting starts from the centre and proceeds towards the surface [114] for embedded nanoparticles, while the melting starts from the surface and proceeds towards the centre for free nanoparticles.…”
Section: Superheating Of Nanoparticlesmentioning
confidence: 99%
“…This suggests that the confining medium, in this case, zeolite NaCaA, has a strong influence on the width of these peaks. Elsewhere it is shown that the increase in the volume of a free cluster with increase in temperature is larger than that for a confined cluster above 29 K (Chitra and Yashonath 1997).…”
Section: Resultsmentioning
confidence: 95%
“…This suggests that the confined cluster spends a larger fraction of time on the saddle points in the potential energy surface as compared to the free cluster. Earlier work on Am3 cluster in the zeolite L has shown that such a cluster will exhibit the phenomenon of inverse surface melting: the inner atoms of the confined Arn3 cluster melt (acquire mobility) even before the outer atoms melt (Chitra and Yashonath 1997). This is in contrast to the surface melting behaviour exhibited by free clusters of medium to large size, where atoms on the outer surface usually melt before the inner core acquires mobility (Cheng and Berry 1992;Kunz and Berry 1993).…”
Section: Starting Configurationmentioning
confidence: 91%